Reduced left ventricular filling following blood volume extraction does not result in compensatory augmentation of cardiac mechanics. Issue 4 (14th February 2018) - Lord, Rachel; MacLeod, David; George, Keith; Oxborough, David; Shave, Rob; Stembridge, Mike
Abstract : New Findings: What is the central question of this study? A reduction in left ventricular (LV) filling, and concomitant increase in heart rate, augments LV mechanics to maintain stroke volume (SV); however, the impact of reduced LV filling in isolation on SV and LV mechanics is currently unknown. What is the main finding and its importance? An isolated decrease in LV filling did not provoke a compensatory increase in mechanics to maintain SV; in contrast, LV mechanics and SV were reduced. These data indicate that when LV filling is reduced without changes in heart rate, LV mechanics do not compensate to maintain SV. Abstract: An acute non‐invasive reduction in preload has been shown to augment cardiac mechanics to maintain stroke volume and cardiac output. Such interventions induce concomitant changes in heart rate, whereas blood volume extraction reduces preload without changes in heart rate. Therefore, the purpose of this study was to determine whether a preload reduction in isolation resulted in augmented stroke volume achieved via enhanced cardiac mechanics. Nine healthy volunteers (four female, age 29 ± 11 years) underwent echocardiography for the assessment of left ventricular (LV) volumes and mechanics in a supine position at baseline and end extraction after the controlled removal of 25% of total blood volume (1062 ± 342 ml). Arterial blood pressure was monitored continuously by a pressure transducer attached to an indwelling radial artery catheter. Heart rate and total peripheral resistance were unchanged from baseline to end extraction, but systolic blood pressure was reduced (from 148 to 127 mmHg). From baseline to end extraction there were significant reductions in left ventricular end‐diastolic volume (from 89 to 71 ml) and stroke volume (from 56 to 37 ml); however, there was no change in LV twist, basal or apical rotation. In contrast, LV longitudinal strain (from −20 to −17%) and basal circumferential strain (from −22 to −19%) were significantly reduced from baseline to end extraction. In conclusion, a reduction in preload during blood volume extraction does not result in compensatory changes in stroke volume or cardiac mechanics. Our data suggest that LV strain is dependent on LV filling and consequent geometry, whereas LV twist could be mediated by heart rate. Abstract :